Accelerated calciprotein crystallization time (T50) is correlated with impaired lung diffusion capacity in systemic sclerosis - Geroldinger-Simic, Marija; Sohail, Azmat; Razazian, Mehdi; Krennmayr, Beatrice; Pernsteiner, Victoria; Putz, Thomas; Lackner, Helmut K.; Pasch, Andreas; Sepp, Norbert; Alesutan, Ioana; Voelkl, Jakob (Frontiers in Immunology, 2024)
Systemic sclerosis (SSc) is a complex auto-immune disease characterized by vascular damage, inflammation, fibrosis and calcinosis, where pulmonary involvement is the leading cause of mortality. Calciprotein particles (CPPs) are increasingly formed upon disbalance of the physiological mineral buffering system and induce pro-inflammatory effects. This exploratory study investigated whether functional indicators of the endogenous mineral buffering system are dysregulated in SSc and linked to disease activity. Methods T50 (calciprotein crystallization test or serum calcification propensity) and hydrodynamic radius of secondary CPPs (CPP2) were determined in serum samples from 78 SSc patients and 44 controls without SSc, and were associated with disease activity markers of SSc.T50 was reduced and CPP2 radius was increased in SSc patients as compared to controls, indicating a deranged mineral buffering system. This was accompanied by slightly higher serum phosphate and PTH levels in SSc patients, while iFGF23 was not significantly modified. Longitudinally, all parameters remained unchanged over time in SSc patients, only iFGF23 increased. While the modified Rodnan skin score showed some inconsistent correlations with mineral buffering indicators, their association was not independent of other factors. However, lower T50 was significantly correlated to reduced lung diffusion capacity and this association remained significant in a multivariate linear regression model.This study provides indications for a disturbed mineral buffering system in SSc. Increased serum calcification propensity (lower T50) is correlated with impaired lung diffusion capacity, suggesting a possible role of deranged mineral buffering in disease progression. Further studies are required to confirm these observations in larger cohorts and to investigate a putative functional relevance.